If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -3 = 27x + 3 Reorder the terms: -3 + 15x = 27x + 3 Reorder the terms: -3 + 15x = 3 + 27x Solving -3 + 15x = 3 + 27x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27x' to each side of the equation. -3 + 15x + -27x = 3 + 27x + -27x Combine like terms: 15x + -27x = -12x -3 + -12x = 3 + 27x + -27x Combine like terms: 27x + -27x = 0 -3 + -12x = 3 + 0 -3 + -12x = 3 Add '3' to each side of the equation. -3 + 3 + -12x = 3 + 3 Combine like terms: -3 + 3 = 0 0 + -12x = 3 + 3 -12x = 3 + 3 Combine like terms: 3 + 3 = 6 -12x = 6 Divide each side by '-12'. x = -0.5 Simplifying x = -0.5
| 4(2x-1)=8x+10 | | 7+3x=4(x-1) | | 9y=4y+10 | | 17x=2x+15 | | 8*ln(7x)=48 | | 4s-20=-3 | | 6x+2=-6+6x | | 3x-6=2x+5(x-1) | | 3x-12=-36 | | 3(2x-1)-(x-4)=2 | | .5(4x-10)+5=x-11 | | -4=4-u/2 | | 6x-3=7x+4 | | 6x+12=4x-18 | | x^3+x^2*y-4*y^2=0 | | 7b-21-8b=2 | | 10+3-6+34= | | 4(x+2)-17=35 | | 3x^2-5x-4-6x+8-x^2= | | -2x=-10-2x | | 2xy+4z-7xy-7z= | | 3r=30r+21 | | 10x=2x+26 | | -3xy+2x-7z= | | 5/8=2m+3/8 | | 5(3n+1)=2(5n-4)+6n | | 7x-8+4=5x-2 | | (8w)(2w^9y^7)(3y^8)= | | 2(u+3v)=4(y-5) | | 7-x+3=9x+10 | | -4-2y+3-y= | | 4y-14-13-y=-9+15 |